2017
DOI: 10.23838/pfm.2017.00184
|View full text |Cite
|
Sign up to set email alerts
|

Old drug, new findings: colistin resistance and dependence of Acinetobacter baumannii

Abstract: Colistin is an old drug, and its use has recently resurged because of increasing antibiotic resistance in gram-negative bacteria such as Acinetobacter baumannii. Although the colistin resistance rates in gram-negative bacteria are currently not high, many colistin-resistant isolates are being identified and the possibility of horizontal transmission of colistin resistance has increased because of the plasmid-borne colistin resistance gene mcr-1 (mobilized colistin resistance). In this review, we have discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 77 publications
(92 reference statements)
4
10
0
1
Order By: Relevance
“…The colonies that survived in colistin-containing media showed different amino acid substitutions, even from the same isolate. Only two amino acid alterations (P170L and S17R in PmrB) have been reported in previous studies [25], but others including mutations in LpxACD were newly identified in this study. Although it is required to investigate if the mutations would be associated with colistin resistance, diverse colistin-resistant subpopulations of the original isolates may have been present prior to the start of experiments.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The colonies that survived in colistin-containing media showed different amino acid substitutions, even from the same isolate. Only two amino acid alterations (P170L and S17R in PmrB) have been reported in previous studies [25], but others including mutations in LpxACD were newly identified in this study. Although it is required to investigate if the mutations would be associated with colistin resistance, diverse colistin-resistant subpopulations of the original isolates may have been present prior to the start of experiments.…”
Section: Discussionmentioning
confidence: 47%
“…Acinetobacter baumannii is a catalase-positive, gram-negative, and opportunistic pathogen responsible for life-threatening infectious disease conditions including pneumonia, sepsis, and meningitis [ 1 ]. Treating A. baumannii infections is challenging due to the remarkable ability of this pathogen to acquire antibiotic resistance [ 2 ]. A. baumannii has also been listed among Priority 1 pathogens for which new antibiotics are urgently needed by World Health Organization (WHO) in 2017 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main mechanism of colistin resistance in A. baumannii is the modification of lipopolysaccharide (LPS) by mutations in PmrA/PmrB two-component system (Ko et al 2017). These mutations cause upregulation of the pmr-CAB operon, which results in the synthesis and addition of positively charged phosphoethanolamine to the LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Colistin-susceptible A. baumannii strains may develop dependence after exposure to colistin in vitro [ 12 , 13 , 14 ]. Colistin dependence is not rare, as many as 32.9% of colistin-susceptible isolates were able to do so [ 14 ], most of them were otherwise multidrug-resistant and able to cause infection in mice [ 15 ].…”
Section: Introductionmentioning
confidence: 99%